The translation of fictive neology through the decades: a case study - Sánchez López, Ana Cristina (Estudios de Traducción, 2025)
Neologisms are a key factor of science fiction and world building, and their proper translation is essential if the complexity of the genre, with its usually multi-layered plot, is to be fully understood in the target language. However, the perception of science fiction and its characteristic futuristic, technological worlds may have changed in last decades due to the breakthroughs in technology and science experienced by societies all around the world. This study extracts the neologisms related to technical and scientific breakthroughs found in four English-written science fiction novels and in their translation and retranslations into Spanish, creates a contrastive corpus and analyses if the approach to their translation has evolved. The novels used are Brave New World (Aldous Huxley, 1932); Nineteen Eighty‑Four (George Orwell, 1949), Fahrenheit 451 (Ray Bradbury, 1953) and Do Androids Dream of Electric Sheep? (Philip K. Dick, 1968).